ANALISIS PENGGUNAAN GAYA BAHASA PADA ANTOLOGI CERPEN "PANCARONA" KARYA SISWA KELAS IX SMP - Dina Amelia Nurhayati; Iis Siti Salamah Azzahra; Indra Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The background of this research is to find out the extent of students understanding in using language styles in learning to compose short stories. The purpose of this study was to analyze the use of language style in a anthology of short stories â€œPancaronaâ€ by Siswa Kelas IX SMPN 2 Cililin. The method used is descriptive qualitative. The data in this study are in the from of quatations obtained from the results of the analysis which show the use of language style. Based on the result of the discussion, it can be concluded that the types of language styles found in the short story anthology book â€œPancaronaâ€ consist of 15 short story titles analyzed, the research found 8 types of language styles used by students when compiling short stories, including the following: 1) There are 15 hyperbolic language types, 8 metaphors, 6 personifications, 4 similes, 2 paradoxes, 1 synesthesia, 1 alliteration, and 1 metonymy. 2) Short storie with the most use of language styles are short stories entitled Cinta tak Terduga and Bad Boy with the use of 6 types of language styles. From a total of 15 short story titles analyzed in the book â€œPancaronaâ€ short story anthology, a total of 38 language styles were obtained.Â